QSAR Studies on the N-Aryl-oxazolidinone-5-carboxamides Against HIV-1 Protease - Mishra, Saloni; Singh, Supriya; Mishra, J.P. (Asian Journal of Chemistry, 2010)
N-Aryl-oxazolidinone-5-carboxamides are new effective target against the HIV-1 protease. Quantitative structure activity relationship (QSAR) has been carried out in this series. The data set was divided into two subsets i.e. training set and test set. The 2D QSAR studies activity is negatively influenced by the resonance effect at position R3. The best QSAR model with good correlation coefficient (r2 = 0.859), of high statistical significance (> 99.9 %) well explained the variance in activity.